A expressão da vontade: relações interétnicas e rebelião indígena nas Missões de Maynas (1685 1698) - Santos, Roberta Fernandes dos (2009)
The Missions of Maynas in Amazônia had been established by the Jesuits in 1638 with the intention of serving to the colonial interests of the Spanish monarchy wich needed to tame territories, to accomplish the occupation of the tamed areas and to prepare the indians for its integration in the colonial system. However, we cannot omit the fact that the performance of the priests in the region not always followed the objectives of the European economic politics, another concern of the missionaries was with the saint Jesuitical mission of conversion of the indians in the New World. The permanence of the Jesuits in the region extended up to 1768 and counted on the establishment of 152 villages, detaches in this work, the reductions established in the river Ucayali that had been under incumbency of the priest Enrique Rickter of 1685 up to 1695 when the Indians rebellion culminated with the murder of the priest. From bibliographical and documental inquiry we intend to analyze the performance of P. Rickter understanding that the contact, the foundation of the villages and their permanence with the Indians of the Ucayali resulted of a negotiation process in which the conditions for the establishment of friendship were imposed by both parts. The unhappiness of the Indian groups demonstrates that in this relation their conditions had not been fulfilled, fact that generated the reasons of the 1695 rebellion and marked the imposition of the indians wishes in cutting the bonds of friendship with the Spanish conquerors